Adolescent drug use before and during U.S. national COVID-19 social distancing policies. (1st September 2021) - Miech, Richard; Patrick, Megan E.; Keyes, Katherine; O'Malley, Patrick M.; Johnston, Lloyd
Highlights: Perceived availability of marijuana and alcohol declined during the pandemic at the largest levels ever recorded in 46 years. Prevalence of adolescent marijuana and alcohol use did not significantly change during the pandemic. These results demonstrate the substantial challenges facing a supply-side approach to the reduction of adolescent substance use. Abstract: Background: How adolescent substance use and perceived availability of substances have changed during the COVID-19 pandemic remain largely unknown. Substantial reduction in availability of substances would present a unique opportunity to consider the supply-side hypothesis that reductions in drug availability will lead to reductions in drug prevalence. Methods: Longitudinal data come from Monitoring the Future and are based on responses from 582 adolescents who were originally surveyed as part of a national sample of 12 th grade students in early 2020, one month before social distancing policies began. They were surveyed again after social distancing policies were implemented, in the summer of 2020. Results: Perceived availability of marijuana and alcohol declined across the two survey waves at the largest levels ever recorded in the 46 years of the project, by an absolute 17 %, p < .01 and 24 %, p < .01, respectively. Despite these declines, prevalence levels did not significantly change across the two waves for marijuana use in the past 30 days or for binge drinking in the past two weeks. Perceived availability of vaping devices significantly declined, from 73 % to 63 %, as did nicotine vaping prevalence in the past 30 days, from 24 % to 17 %. Conclusions: Perceived availability of marijuana, alcohol, and vaping devices declined at historic rates during the pandemic of 2020. Lack of accompanying reductions in prevalence for marijuana and binge drinking demonstrates the substantial challenges facing a supply-side approach to the reduction of adolescent use of these substances.